Spindle-cell sarcoma of the heart: A rare cause for a cardiac mass - Mehra, Sanjay; Ibrahim, Osman; Moshiri, Mariam; Cahill, John; Bhargava, Puneet (My University, 2012)
Primary cardiac tumors are rare and are usually diagnosed at an advanced stage due to nonspecific symptoms. We report a 46-year-old female who presented to our institution with shortness of breath and was diagnosed with a cardiac spindle-cell tumor. Wide surgical resection is the cornerstone for therapy for cardiac sarcomas. Our patient was considered inoperable due to the extent of the tumor.